2014
DOI: 10.1016/j.compfluid.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oscillatory instability in lid driven cavity flows using lattice Boltzmann method

Abstract: In the present work, lattice Boltzmann method (LBM) is applied for simulating flow in a three-dimensional lid driven cubic and deep cavities. The developed code is first validated by simulating flow in a cubic lid driven cavity at 1000 and 12000 Reynolds numbers following which we study the effect of cavity depth on the steady-oscillatory transition Reynolds number in cavities with depth aspect ratio equal to 1, 2 and 3. Turbulence modeling is performed through large eddy simulation (LES) using the classical S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
2
22
1
Order By: Relevance
“…In the case of the supercritical Hopf bifurcation the absolute value of the components of the perturbation velocity field shows how the oscillation amplitude is distributed in the flow region. As mentioned, some previous works [10,14,15,18] concluded that the steady- Figure 5 contains also perturbation patterns of the two-dimensional lid-driven cavity flow. Note that the absolute values of the perturbation patterns are quite similar to the previously reported ones [16,17], as well as to the oscillation amplitude patterns reported in Fig.…”
Section: Patterns Of the Most Unstable Perturbationsmentioning
confidence: 75%
See 1 more Smart Citation
“…In the case of the supercritical Hopf bifurcation the absolute value of the components of the perturbation velocity field shows how the oscillation amplitude is distributed in the flow region. As mentioned, some previous works [10,14,15,18] concluded that the steady- Figure 5 contains also perturbation patterns of the two-dimensional lid-driven cavity flow. Note that the absolute values of the perturbation patterns are quite similar to the previously reported ones [16,17], as well as to the oscillation amplitude patterns reported in Fig.…”
Section: Patterns Of the Most Unstable Perturbationsmentioning
confidence: 75%
“…Clearly, the grid refinement in the 3D computations is strongly restricted compared to the 2D case, by both available computer memory and affordable CPU time. At the same time, the critical Reynolds number in the 3D case [10][11][12][13][14][15][16][17][18] is approximately 4 times smaller than that of the 2D case, which allows us to expect a better convergence on coarser grids.…”
Section: D Lid Driven Cavity Revisitedmentioning
confidence: 97%
“…This flow pattern is very similar to a lid-driven cavity flow. [32][33] The location of the vortex center and the shape of the vortex in the stator cavities depends on how exactly it is being generated by the rotor and its cavities. Also in the rotor cavities, the liquid is strongly sheared while -at the same time -it moves with the rotor in the circumferential direction.…”
Section: Flow Fields In the Dynamic Mixermentioning
confidence: 99%
“…An alternative approach to computationally solve threedimensional lid-driven cavity flow is to use lattice Boltzmann methods coupled with SGS turbulence models to simulate flows up to Re = 1.2 × 10 4 [13,14]. Lattice Boltzmann methods for lid-driven cavity flow have previously used simple boundary conditions, such as bounce-back for the Dirichlet condition at the stationary cavity walls and interpolation schemes [14][15][16], as well as regularized schemes to improve stability [17]. This improvement in stability for LBM is a key issue, since the time complexity is on the order of L 4 .…”
Section: Figmentioning
confidence: 99%